2023
DOI: 10.1155/2023/5176645
|View full text |Cite
|
Sign up to set email alerts
|

The Diabetic Lung Can Be Ameliorated by Citrullus colocynthis by Reducing Inflammation and Oxidative Stress in Rats with Type 1 Diabetes

Abstract: Background. Diabetes impacts various organs in the body and some reports showed that the lung is also affected by diabetes, and an imbalance of inflammation and oxidative stress may participate to diabetic lung impairments. The present study is conducted to assess the impacts of Citrullus colocynthis (CC) on some aspects of these impairments. Methods. Frothy two male Wistar rats (3-4 months old and weighing 200–250 g) were used in the present research. Animals were divided into 3 groups of control, Diabetes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Also, Dennis et al reported that increased TNFα levels are associated with inadequate glucose control in T2D and impaired lung function [ 41 ]. In another study, it has been shown that the levels of IL-6 and IL-17 were increased in diabetic lungs [ 42 ]. Diabetes is a pro-inflammatory state associated with airway inflammation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, Dennis et al reported that increased TNFα levels are associated with inadequate glucose control in T2D and impaired lung function [ 41 ]. In another study, it has been shown that the levels of IL-6 and IL-17 were increased in diabetic lungs [ 42 ]. Diabetes is a pro-inflammatory state associated with airway inflammation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…After euthanizing the animals and removing the heart, the right lung was clamped, and 1 ml of phosphate-buffered saline (PBS) was injected using a syringe through a tracheal cannula into the left lung. Following a 2-minute interval, the infused liquid was lavaged and subsequently stored at − 80 °C [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to the World Health Organization (WHO), the number of diabetics was 171 million in 2000 and is estimated to reach 366 million by 2030 2 . Diabetes is considered a leading risk factor for cardiomyopathy, neuropathy, nephropathy, and retinopathy and represents a significant economic burden for countries worldwide 3 5 .…”
Section: Introductionmentioning
confidence: 99%